2005
DOI: 10.3748/wjg.v11.i10.1529
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate aminotransferase-immunoglobulin complexes in patients with chronic liver disease

Abstract: AIM:To determine the complex of AST and immunoglobulin and to investigate its clinical significance in patients with liver disease. METHODS:The complex of AST and immunoglobulin was determined by encounter immunoelectrophoresis and its clinical significance was investigated in 128 patients with liver disease. RESULTS:AST was bound to immunoglobulin of antiimmunoglobulin A (IgA) class, but any binding to antiimmunoglobulin G and anti-immunoglobulin M classes was not observed. Although the incidence of ASTimmuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
4
11
0
3
Order By: Relevance
“…In general, autoantibodies which form macroanalyte complexes are not believed to be disease-causing although cases associated with autoimmune disorders have been described [16,17] and reports suggesting an association between the presence of autoantibodies against cTnI and cardiomyopathy have been published [18][19][20]. Based on current evidence, the main problem caused by a circulating macroanalyte is that it leads to multiple, possibly invasive, investigations in search of a cause.…”
Section: Introductionmentioning
confidence: 99%
“…In general, autoantibodies which form macroanalyte complexes are not believed to be disease-causing although cases associated with autoimmune disorders have been described [16,17] and reports suggesting an association between the presence of autoantibodies against cTnI and cardiomyopathy have been published [18][19][20]. Based on current evidence, the main problem caused by a circulating macroanalyte is that it leads to multiple, possibly invasive, investigations in search of a cause.…”
Section: Introductionmentioning
confidence: 99%
“…We examined whether the healthy control group and the patient groups differed in the amounts of ALTIgA complex and found that the HCC and LC groups had higher amounts of the ALT-IgA complex than the other groups [median A 450 , 1.7 (interquartile range, 1.4 -1.9) vs 1.3 (interquartile range, 0.9 -1.6)] (see figure in the online Data Supplement); however, the concentrations of the ALT-IgA complex were significantly higher in all of the patient groups compared with the control group (all P Ͻ 0.05). Recently, several reports described high IgA concentrations in serum and a high incidence of IgA nephropathy in LC patients and indicated that the amount of aspartate aminotransferaseIgA complexes increased as liver disease progressed (12,13 ). Other modifications of serum ALT, such as glycation or fragmentation by proteolysis, could inhibit the interaction of ALT with a cofactor or substrate or could convert the functional dimeric protein to a monomeric form (8,14 ).…”
Section: Resultsmentioning
confidence: 99%
“…encontró presencia de macro-AST en 90% de los pacientes con carcinoma hepatocelular, 41,8% de pacientes con hepatitis crónica, 62% de pacientes con cirrosis y en 66% de las hepatitis alcohólicas 6,18 . Los macro-complejos enzimáticos se pueden medir con distintas técnicas.…”
Section: Elevación Aislada De La Aspartato-aminotransferasa (Ast)unclassified